Current role of saphenous vein graft in coronary artery bypass grafting - Raza, Sajjad (Indian J Thorac Cardiovasc Surg, 2018)
Saphenous vein was the conduit used in the first series of coronary artery bypass grafting (CABG), and, with the exception of surgical revascularization of the left anterior descending artery, it remains the most commonly used bypass conduit. However, its durability and longevity are not ideal. Arterial grafts have better patency than saphenous vein grafts and therefore should be preferred over them. However, in certain situations, like grafting right coronary arteries with lesser degree of proximal stenosis and higher competitive flow, or in certain patient populations, like those at very high risk of wound infections and octogenarians, arterial grafting may not be the best option and saphenous vein grafting should be considered instead.